PENGELOLAAN KEUANGAN UMKM JAJANAN KHAS GARUT TEKWAN TARENG35 DI KARAWANG JAWA BARAT - Amelia Nurafiah; Ropina Sitanggang; Dwi Epty Hidayaty; Santi Pertiwi Hari Sandi (PT Naureen Digital Education, 2023)
MSME is a business potential that is highly encouraged by the government. Where the performance of MSMEs is very necessary so that the goals of MSMEs are met in terms of HR competencies owned by MSMEs determine the course of MSME performance, the next stage is in the form of a Simple Financial Management Model. The current condition of the macro environment is not very conducive for the implementation of MSME activities. MSMEs also carry out and form business networks to expand MSME partnerships, and facilitate cooperation with other parties so that MSME performance can run well. Efforts to improve performance are very important especially those related to HR competence, macro environmental conditions and business networks carried out by SMEs. The purpose of this study is to determine the effect of HR competence and how to manage its finances, macro environment and business networks on the performance of food SMEs in Tekwan Tareng35 Karawang. So this research is useful to add references about the condition of MSME performance related to HR compensation and financial management, macro environment and business networks. From the results of this research, it was carried out using two methods, namely direct observation and interviews at one of the eating businesses, namely Tekwan Tareng35, to be precise in front of Singaperbangsa Karawang University, it can be seen that at this time in 2020 the Tekwan Tareng35 business already has 4 HR staff. The discussion of this research is to analyze and describe the empowerment of Micro, Small and Medium Enterprises (MSMEs) human resources from the start of the business, business success, business failure to survive until now. Conclude financial management that is commonly used and provide information regarding how to use working capital management for Mr. Jaky's business so that the financial management used can help increase sales of food made by Mr